Pre‐emptive versus non pre‐emptive kidney transplantation for end‐stage kidney disease - Olarte Parra, Camila (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review aims to look at the benefits and harms of pre‐emptive kidney transplantation compared with kidney transplantation after dialysis for patients with ESKD.